Gastroschisis Spiral-like Closure with Umbilical Cord in a Limited-resource Setting: A Case Report - Giulia Reggiani; Damiano Pizzol; Daniele Trevisanuto; Mario Antunes (EL-Med-Pub, 2018)
Gastroschisis is one of the most frequent congenital surgical problems in fetuses and neonates, with a continuously increasing incidence worldwide. In limited-resource settings, the management of this condition is difficult, and the mortality rates are much higher than those observed in high-income countries. We report the case of a newborn with gastroschisis and viscero-abdominal disproportion, submitted to abdominal wall closure through utilization of umbilical cord tissue. This technique has not already been applied in low-resource countries, where it can show advantages such as lower risk of abdominal compartment syndrome and local infection, high availability, and low cost.